An innovative synthesis approach for Na A. Zeolite: A new pathway for enhanced performance, wastewater treatment, and antibacterial applications - Mutairah S. Alshammari; Amro H. Mohamed; Samah A. Mohamed; Hussein M. Ahmed (PLoS ONE, 2025)
Wastewater treatment is essential for protecting water resources and public health. Zeolite-based adsorbents offer an effective and sustainable solution for this purpose, providing high selectivity and regeneration potential. Zeolites are inorganic, highly crystalline, micro-porous materials composed of aluminotecto-silicates (SiO₄ and AlO₄ tetrahedral). Synthetic zeolites are commercially favored over natural ones due to their higher purity, crystallinity, and uniform pore size. Na A. zeolite (NaAZ) is a type of synthetic zeolite widely used in various applications, including wastewater treatment, due to its excellent adsorption and ion-exchange properties. This study focus on synthesize zeolite A from meta-kaolinite using a wet chemical method. The synthesis involves a hydrothermal process in which chemical reagents are mixed in an aqueous medium and heated under controlled conditions. The resulting (NaAZ) was characterized using Brunauer-Emmett-Teller (BET) surface area analysis, Fourier Transform Infrared Spectroscopy (FT-IR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray Spectroscopy (EDX). This study evaluates the synthesized (NaAZ) for the removal of chemical oxygen demand from synthetic wastewater. Various parameters affecting adsorption such as contact time pH, temperature, and adsorbent dosage were investigated. The optimized conditions were then applied to real wastewater, and the material was further tested for its antitoxic and antibacterial properties. The in vitro antibacterial activity of NaAZ was assessed against both Gram-positive bacteria (Bacillus subtilis ATCC 6633, Staphylococcus aureus ATCC 6538, Enterococcus faecalis ATCC 19433) and Gram-negative bacteria (Escherichia coli ATCC 25922, Enterobacter aerogenes ATCC 13048, Pseudomonas aeruginosa ATCC 15442). Under optimal conditions contact time (40 min), pH (6–7), and adsorbent dosage (0.25 g) the removal efficiencies for COD, TSS, TKN, and PO₄3⁻ were 90.69%, 90.41%, 73.75%, and 68.85%, respectively.